The combined effect of enterprise risk management and diversification on property and casualty insurer performance - Ai, Jing, author; Bajtelsmit, Vickie, author; Wang, Tianyang, author; Journal of Risk and Insurance, publisher (Colorado State University. Libraries, 2016)
In a well‐designed enterprise risk management (ERM) program, the firm integrates risk management into the strategic planning process, addressing strategic, financial, operational, and hazard risks under a single overarching process. This is particularly important to large financial firms, such as property and casualty (P&C) insurers, which face a diverse set of risks. Using a sample of P&C insurers with S&P ERM quality ratings from 2006 to 2013, we find that the quality of a firm's ERM is a significant determinant of P&C insurer performance and that, for firms with high‐quality ERM programs, product line diversification has a significant positive effect on performance.
Published as: Journal of Risk and Insurance, vol. 85, no. 2, June 2018, pp. 513543. https://doi.org/10.1111/jori.12166.
Keywords: enterprise risk management (ERM); diversification; property and casualty; insurance company performance